Dairy Farmer Central. - Monash University (Melbourne, Victoria: Monash University)
"The central source of information for programs, initiatives and events available for dairy farmers and their communities."
Title from title screen (viewed on 2 September 2019)
Mode of access: Available Online. Address as at 16/09/2019
Selected for archiving
Keywords: Dairy farmers -- Australia; Dairy farming -- Australia; Australian